The Effect of a Rehabilitation Program on Improving Knee Joint Range of Motion in Injured Basketball Players - Suhail, Marwa; Hussein , Soha (Journal of Physical Education, 2025)
Sports Medicine is unique as the injuries and treatments require specialized considerations in both diagnosis, treatment, and recovery. The frequency of these injuries has increased in athletes, especially in sports that require contact with the opponent, like basketball. This study is important in that it intends to be able to perform pain-free training until the back to baseline with physiotherapy devices, isometric exercises and moderate progressive load increases from easy to difficult. The following is the central research question: because some injuries are such that a patient cannot have control of a given range of motion, and this will weaken the knee. Precisely, there is a critical demand to develop targeted rehabilitation for restoration of knee function in athletes, mainly on basketball players that meet the game’s requirement. One of the suggested approaches is to apply training doses at different intensities to help the joint and surrounding muscles recover their natural strength, build up reserves and get back to normal resistance capacity. Thus the purpose of this study is to create a re- habilitation program with an androgenic/anabolic enhancing effect, helping post trauma basketball players im- prove their knee joint mobility.